The Dark Galaxy Hypothesis. Issue 5 (December 2018) - Weisberg, Michael; Jacquart, Melissa; Madore, Barry; Seidel, Marja
Abstract: Gravitational interactions allowed astronomers to conclude that dark matter rings all luminous galaxies in gigantic halos, but this only accounts for a fraction of the total mass of dark matter believed to exist. Where is the rest? We hypothesize that some of it resides in dark galaxies, pure dark matter halos that either never possessed or have totally lost their baryonic matter. This article explores methodological challenges that arise because of the nature of observation in astrophysics and examines how the blend of observation, simulation, and theory we call the Observing the Invisible approach might make detecting such dark objects possible.